Evaluation of processing effects on anthocyanin content and colour modifications of blueberry (Vaccinium spp.) extracts: Comparison between HPLC-DAD and CIELAB analyses. (1st October 2017) - Cesa, Stefania; Carradori, Simone; Bellagamba, Giuseppe; Locatelli, Marcello; Casadei, Maria Antonietta; Masci, Alessandra; Paolicelli, Patrizia
Highlights: Ultraturrax® processing showed the highest anthocyanin content in blueberry puree. Rapid pasteurization prevented anthocyanin degradation after blueberry grinding. Blueberry extract colour was affected by homogenizing/heating treatments. Colour nuance highly correlated respect to delphinidin/malvidin glycosides ratio. Abstract: Colour is the first organoleptic property that consumers appreciate of a foodstuff. In blueberry ( Vaccinium spp . ) fruits, the anthocyanins are the principal pigments determining the colour as well as many of the beneficial effects attributed to this functional food. Commercial blueberry-derived products represent important sources of these healthy molecules all year round. In this study, blueberries were produced into purees comparing two homogenization methods and further heated following different thermal treatments. All the supernatants of the homogenates were monitored for pH. Then, the hydroalcoholic extracts of the same samples were characterized by CIELAB and HPLC-DAD analyses. These analytical techniques provide complementary information on fruit pigments content as a whole and on quali-quantitative profile of the single bioactive colorants. These data could be very interesting to know the best manufacturing procedure to prepare blueberry-derived products, well accepted by the consumers, while maintaining their healthy properties unaltered.